Coaching Stressors in a Division II Historically Black University - Robbins, Jamie E.; Gilbert, Jenelle N.; Clifton, Alexandra M. (Journal of Intercollegiate Sport, 2015)
Recently, studies have addressed the stressful nature of the coaching profession, identifying a multitude of stressors among coaches for Division I, national, and international programs (Durand-Bush, Collins, & McNeill, 2012; Frey, 2007; Levy, Nicholls, Marchant, & Polman, 2009; Olusoga, Butt, Hays, & Maynard, 2009). The purpose of this study was to further the research by studying coaches at a Historically Black College/University (HBCU) and Division II (DII) athletic program. Participants included seven head and five assistant coaches across seven sports. All coaches were interviewed, based on a preexisting interview guide (Olusoga et al., 2009). Data were content analyzed using previously agreed upon procedures and submitted in NVivo for further examination (Côté, Salmela, Baria, & Russell, 1993). Three higher order themes termed Interpersonal, Intrapersonal, and Contextual Stressors emerged and were composed of 16 lower order themes. The most commonly cited interpersonal stressors included athletes, expectations of others, and administration. Performance outcome and lack of control were the most common intrapersonal stressors. Finally, schedule, lack of resources, and job security were the most common contextual stressors. These findings emphasize the stressful nature of the job and the need to identify means for minimizing stressors to improve the athletic experience for all involved.